Response of water-biochar interactions to physical and biochemical aging. (November 2022) - Goñi-Urtiaga, Asier; Courtier-Murias, Denis; Picca, Giuseppe; Valentín, Juan L.; Plaza, César; Panettieri, Marco
Abstract: Biochar aging may affect the interactions of biochar with water and thus its performance as soil amendment; yet the specific mechanisms underlying these effects are poorly understood. By means of FTIR, N2 adsorption, Hg intrusion porosimetry, thermogravimetric analysis, 13 C solid state nuclear magnetic resonance (NMR) and 1 H NMR relaxometry, we investigated changes in the chemistry and structure of biochar as well as its interaction with water after biochar aging, both physical (simulated by ball-milling) and biochemical (simulated by co-composting). Three different porosities of biochar were examined: <5 nm, 1 μm and 10 μm diameter sizes. Physical aging caused the disappearance of the porosity at 10 μm. With biochemical aging, biochar underwent an enrichment of oxygenated functional groups either as a result of surface functionalisation processes or by the deposition of fresh organic matter layers on the surface and pores of biochar. 1 H NMR relaxometry revealed that the proportion of water strongly interacting with biochar increased with both physical and biochemical aging. Although biochemical aging significantly altered the composition of biochar surface and modulates its interaction with water, 1 H NMR relaxometry proved that physical aging had a relatively stronger influence on water mobility and dynamics in biochar, lowering both T1 and T2 relaxation times in the initial contact times of biochar and water. Graphical abstract: Image 1 Highlights: We simulated physical (milling) and biochemical (composting) aging of biochar. Physical aging removes the 10 μm size macroporosity of biochar. Biochemical aging induces the functionalisation of biochar surfaces. Combined aging decreases 1 H NMR relaxation times in wet biochar. Biochar aging strengthen the water-biochar interactions.